Advanced glycation end products-induced insulin resistance involves repression of skeletal muscle GLUT4 expression - Pinto-Junior, Danilo C.; Silva, Karolline S.; Michalani, Maria L.; Yonamine, Caio Y.; Esteves, Joao V.; Fabre, Nelly T.; Thieme, Karina; Catanozi, Sergio; Okamoto, Maristela M.; Seraphim, Patricia M. [UNESP]; Correa-Giannella, Maria L.; Passarelli, Marisa; et al. (Nature Publishing Group, 2018)
Little is known about advanced glycation end products (AGEs) participation in glucose homeostasis, a process in which skeletal muscle glucose transporter GLUT4 (Scl2 alpha 4 gene) plays a key role. This study investigated (1) the in vivo and in vitro effects of AGEs on Slc2 alpha 4/GLUT4 expression in skeletal muscle of healthy rats, and (2) the potential involvement of endoplasmic reticulum and inflammatory stress in the observed regulations. For in vivo analysis, rats were treated with advanced glycated rat albumin (AGE-albumin) for 12 weeks; for in vitro analysis, soleus muscles from normal rats were incubated with bovine AGE-albumin for 2.5 to 7.5 hours. In vivo, AGE-albumin induced whole-body insulin resistance; decreased (similar to 30%) Slc2 alpha 4 mRNA and GLUT4 protein content; and increased (similar to 30%) the nuclear content of nuclear factor NF-kappa-B p50 subunit (NFKB1), and cellular content of 78 kDa glucose-regulated protein (GRP78). In vitro, incubation with AGE-albumin decreased (similar to 50%) the Slc2 alpha 4/GLUT4 content; and increased cellular content of GRP78/94, phosphorylated-IKK-alpha/beta, nuclear content of NFKB1 and RELA, and the nuclear protein binding into Slc2 alpha 4 promoter NFKB-binding site. The data reveal that AGEs impair glucose homeostasis in non-diabetic states of increased AGEs concentration; an effect that involves activation of endoplasmic reticulum-and inflammatory-stress and repression of Slc2 alpha 4/GLUT4 expression.